Comparison of artificial rearing systems using clinical and hematological parameters: A preliminary study - Galotta, Maria Laura (2018)
Comparison of clinical and hematological profile of Anglo Nubian kids wasperformed under three different rearing systems. Animals were separated from their dams and rearing from birth until pre-weaning at 24 days of age. Kids were fed with goat milk, reconstituted cow powder milk and reconstituted cow powder milk with enrofloxacin in sub-therapeutic doses. Clinical exam and blood analysis were performed at 3, 10 and 21 days of treatment. As a result, body weight did not show significant differences between treatments. However, values of cardiac frequency, cholesterol, urea, serumalkaline phosphatase and segmented neutrophils (%) were higher than the reference values. These results could be explained considering the physiological state and age of the animals. During this experiment, the use of diet supplemented with enrofloxacin did not generate substantial benefits in the animals that received it. In addition, the use of antibiotics in farms needs to be reconsidered in order to avoid negative environmental effects